Mesenchymal stem cells protect from acute liver injury by attenuating hepatotoxicity of liver natural killer T cells in an inducible nitric oxide synthase‐ and indoleamine 2, 3‐dioxygenase‐dependent manner. (2nd August 2017) - Gazdic, Marina; Simovic Markovic, Bojana; Vucicevic, Ljubica; Nikolic, Tamara; Djonov, Valentin; Arsenijevic, Nebojsa; Trajkovic, Vladimir; Lukic, Miodrag L.; Volarevic, Vladislav
Abstract: The effects of mesenchymal stem cells (MSCs) on the phenotype and function of natural killer T (NKT) cells is not understood. We used concanavalin A (Con A) and α‐galactosylceramide (α‐GalCer)‐induced liver injury to evaluate the effects of MSCs on NKT‐dependent hepatotoxicity. Mouse MSCs (mMSCs) significantly reduced Con A‐ and α‐GalCer‐mediated hepatitis in C57Bl/6 mice, as demonstrated by histopathological and biochemical analysis, attenuated the influx of inflammatory [T‐bet +, tumour necrosis factor‐α (TNF‐α), interferon‐γ (IFN‐γ)‐producing and GATA3 +, interleukin‐4 (IL‐4)‐producing] liver NKT cells and downregulated TNF‐α, IFN‐γ and IL‐4 levels in the sera. The liver NKT cells cultured in vitro with mMSCs produced lower amounts of inflammatory cytokines (TNF‐α, IFN‐γ, IL‐4) and higher amounts of immunosuppressive IL‐10 upon α‐GalCer stimulation. mMSC treatment attenuated expression of apoptosis‐inducing ligands on liver NKT cells and suppressed the expression of pro‐apoptotic genes in the livers of α‐GalCer‐treated mice. mMSCs reduced the cytotoxicity of liver NKT cells against hepatocytes in vitro . The presence of 1‐methyl‐dl ‐tryptophan, a specific inhibitor of indoleamine 2, 3‐dioxygenase (IDO), or l ‐N G ‐monomethyl arginine citrate, a specific inhibitor of inducible nitric oxide synthase (iNOS), in mMSC‐conditioned medium injected into α‐GalCer‐treated mice, counteracted the hepatoprotective effect of mMSCs in vivo and restored pro‐inflammatory cytokine production and cytotoxicity of NKT cells in vitro . Human MSCs attenuated the production of inflammatory cytokines in α‐GalCer‐stimulated human peripheral blood mononuclear cells in an iNOS‐ and IDO‐dependent manner and reduced their cytotoxicity against HepG2 cells. In conclusion, MSCs protect from acute liver injury by attenuating the cytotoxicity and capacity of liver NKT cells to produce inflammatory cytokines in an iNOS‐ and IDO‐dependent manner.